Positioning Art Cinema: Film and Cultural Value, by Geoff King - Fátima Chinita (Alphaville: Journal of Film and Screen Media, 2021)
In Geoff King’s most recent book, Positioning Art Cinema: Film and Cultural Value, the author “positions” art cinema not principally in industrial terms, but rather as a field of cultural production according to Pierre Bourdieu’s theories. Thus, he claims that art cinema is the object of a cultural valorisation. From the outset, the book seems to be an exploration of art cinema in that it conjoins the market/industry with the films’ properties and audience reception (7). It thus offers an effective combination of film analysis and industry-oriented reporting.